Establishment of glioma cell line from freshly clinical sample of HUSM - Nurhidayah, Ab. Rahim (Universiti Sains Malaysia, 2008)
A human malignant continuous cell line, named as GBM N was established from a patient diagnosed with recurrents glioblastoma multiforme which is grade IV glioma. This primary cell line has been serially subcultured until 6th passage in the standard culture media that presenting the existence of various marker. The aim of this study is to assess the morphology of cultured glioblastoma multiforme cells as well as to apply the confirmatory technique such as immunocytochemistry and western blotting method in order to confirm the biological and immunological characteristic of gliomas. Immunocytochemistry finding indicate this cell line retain the expression of Glial Fibrillary Acid Protein (GF AP) despite some previous study show no GF AP are exist in established glioma cell line. However, our study suggests, to prove the existence of GF AP in glioma cell line; we need to culture and subculture until 50th passage in where only the specific protein marker will be presented. Another technique used to confirm the establishment of glioma cell line is western blotting method which serves as total protein study in explaining the biology of tumor as well as to identify the protein that are very potential to cause human disease. We believe that the information regarding the establishment of GBM IV cell line will give benefits to all research community especially who have some interest to cellular and molecular study of cancer with the main purpose to improve glioma's treatment.